Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik - Santi Mulyana, Sri; Susanta, Agus; Sumardi, Hari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the extent to which the Problem Based Learning (PBL) model influences problem-solving ability. The type of research used is experimental research with a Pretest-Posttest Control Group Design. The research subjects were tenth-grade high school students who were divided into two groups: the experimental class, which received learning using the PBL model, and the control class, which received conventional learning. Data were collected through a problem-solving ability test and analyzed using the t-test. The results showed that the problem-solving ability of students taught with the PBL model was better than that of students taught with conventional methods. In addition, PBL learning also enhanced students’ teamwork skills and fostered a sense of responsibility in solving the given problems. Therefore, the PBL model can be considered an alternative in mathematics learning to improve students’ problem - solving abilities. Keywords: PBL; Problem Solving Skills; Mathematics Learning